AN EXPERIMENT ON INNOVATION AND COLLUSION. (21st March 2019) - Smyth, Andrew
Abstract : This paper examines the relationship between product innovation and the success of price collusion using novel laboratory experiments. Average market prices in low innovation (LO) experiments are significantly higher than those in high innovation, but otherwise identical experiments. This price difference is attributed to LO experimental subjects' greater common market experience. The data illustrate how collusion can be perceived as the "only way to make it" in LO markets where product innovation is not a viable strategy for increasing profits. They suggest that product homogeneity can be a proximate cause, and product innovation an ultimate cause, of collusion. ( JEL L41, L10, C92)